Free‐Standing Nanoarrays with Energetic Electrons and Active Sites for Efficient Plasmon‐Driven Ammonia Synthesis. Issue 24 (13th May 2022) - Jiang, Weiyi; Zhang, Haona; An, Yang; Mao, Yuyin; Wang, Zeyan; Liu, Yuanyuan; Wang, Peng; Zheng, Zhaoke; Wei, Wei; Dai, Ying; Cheng, Hefeng; Huang, Baibiao
Abstract: Direct ammonia (NH3 ) synthesis from water and atmospheric nitrogen using sunlight provides an energy‐sustainable and carbon‐neutral alternative to the Haber–Bosch process. However, the development of such a route with high performance is impeded by the lack of effective charge transfer and abundant active sites to initiate the nitrogen reduction reaction (NRR). Here, the authors report efficient plasmon‐induced photoelectrochemical (PEC) NH3 synthesis on the hierarchical free‐standing Au/K x MoO3 /Mo/K x MoO3 /Au nanoarrays. Endowed with energetically hot electrons and catalytically active sites, the plasmonic nanoarrays exhibit an efficient PEC NH3 synthesis rate of 9.6 µg cm −2 h −1 under visible light irradiation, which is among the highest PEC NRR systems. This work demonstrates the rationally designed plasmonic nanoarrays for highly efficient NH3 synthesis, which paves a new path for PEC catalytic reactions driven by surface plasmons and future monolithic PEC devices for direct artificial photosynthesis. Abstract : Free‐standing plasmonic nanoarrays are designed for efficient and monolithic photoelectrochemical (PEC) nitrogen reduction toward ammonia (NH3 ) synthesis, especially under visible light irradiation. Intriguingly, the integration of both energetic hot electrons from plasmonic K x MoO3 nanoarrays and catalytically active sites of Au nanoparticles enables the Au/K x MoO3 /Mo/K x MoO3 /Au nanoarrays to exhibit a high‐performance plasmon‐driven PEC NH3 synthesis activity.